2020
DOI: 10.3389/fpls.2020.574881
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and Its Interaction With Ethylene Control Adventitious Root Formation and Development in Apple Rootstock

Abstract: Adventitious root (AR) formation is indispensable for vegetative asexual propagation. Indole-3-butyric acid (IBA) functioned indirectly as precursor of IAA in regulating AR formation. Ethylene affects auxin synthesis, transport, and/or signaling processes. However, the interactions between auxin and ethylene that control AR formation in apple have not been elucidated. In this study, we investigated the effects of IBA and its interaction with ethylene on AR development in apple. The results revealed that IBA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The dash lines represent the endogenous hormone response to exogenous hormone application. Green letters represent references 1–10: 1) Ford et al (2002) ; 2) de Almeida et al (2015) ; 3) de Almeida et al (2015) ; 4) Fett-Neto et al (2001) ; 5) Harfouche et al (2007) ; 6) Liu et al (2021) ; 7) Liu et al (2021) ; 8) Bai et al (2020) ; 9) Kilkenny et al (2012) ; 10) Munir et al (2021) . The arrows and “T” at the end of lines represent positive and negative regulation, respectively.…”
Section: Adventitious Root Formation Is Controlled By Endogenous Horm...mentioning
confidence: 99%
See 1 more Smart Citation
“…The dash lines represent the endogenous hormone response to exogenous hormone application. Green letters represent references 1–10: 1) Ford et al (2002) ; 2) de Almeida et al (2015) ; 3) de Almeida et al (2015) ; 4) Fett-Neto et al (2001) ; 5) Harfouche et al (2007) ; 6) Liu et al (2021) ; 7) Liu et al (2021) ; 8) Bai et al (2020) ; 9) Kilkenny et al (2012) ; 10) Munir et al (2021) . The arrows and “T” at the end of lines represent positive and negative regulation, respectively.…”
Section: Adventitious Root Formation Is Controlled By Endogenous Horm...mentioning
confidence: 99%
“…In apple ( Malus domestica Borkh.) propagation, the rooting rate in cutting is significantly higher after treatment under 3 g/L IBA with 50 mM H 2 O 2 since H 2 O 2 significantly enhances the effect of IBA on rooting ( Xiao et al, 2014 ), or only with 3 g/L IBA ( Li X et al, 2021 ) for 1 min and then inserted into fine sand and incubated in a mist solar greenhouse, and study has demonstrated that IBA stimulates the production of Eth to stimulate AR formation in apple rootstock propagation ( Bai et al, 2020 ; Devi et al, 2021 ). Olive is one of the hard-to-rooting plants, the hardwood cuttings of olive ( Olea europaea ‘Manzanilla') treated under 3 g/L IBA showed a 1.8-fold increase in rooting rate ( Khajehpour et al, 2014 ).…”
Section: Application Of Exogenous Auxin In Cutting and Tissue Culture...mentioning
confidence: 99%
“…Our previous studies have demonstrated that 10 μM ETH could significantly induce adventitious root development in cucumber and marigold ( Tagetes erecta L.) [ 1 , 15 , 16 ]. Moreover, ETH is associated with other signal molecules, such as nitric oxide (NO), auxin, and calcium ions (Ca 2+ ) in the promotion of adventitious rooting [ 1 , 8 , 17 , 18 ]. For example, NO could be involved in ETH-promoting adventitious root development by enhancing the activities of nitric oxide synthase (NOS) and nitrate reductase (NR), and by regulating rooting-related genes [ CsDNAJ-1 and calcium-dependent protein kinases 1/5 ( CsCDPK1/5) ] [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…rootstock by regulating ETH synthesis. Both auxin and ETH inhibitors significantly prevented adventitious rooting in apple [ 17 ]. Auxin increased the transcript levels of ETH biosynthesis genes, including 1-aminocyclopropane-l-carboxylic acid synthase (ACS) and ACC oxidase (ACO), which resulted in the retention of ETH [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, inappropriate conditions including injury and stress promote AR formation. Recent results revealed that AR formation was positively regulated by plant hormones and signaling molecules, such as abscisic acid (ABA) [ 2 ], auxin [ 3 ], brassinolide (BR) [ 4 ], gibberellin (GA) [ 5 ], ethylene [ 6 ], hydrogen peroxide (H 2 O 2 ) [ 7 ], nitric oxide (NO) [ 8 ], carbon monoxide (CO) [ 9 ] and hydrogen sulfide (H 2 S) [ 10 ] Additionally, molecular evidence illustrated that auxin- and ethylene-related genes and proteins are closely associated with the initiation and development of AR [ 11 ]. The complex responses regulated by these hormones, signaling molecules, genes and proteins are most likely to be achieved by a more detailed AR signaling process.…”
Section: Introductionmentioning
confidence: 99%